Nutritional Ketosis Increases NAD+/NADH Ratio in Healthy Human Brain: An in Vivo Study by 31P-MRS - Xin, Lijing; Ipek, Özlem; Beaumont, Maurice; Shevlyakova, Maya; Christinat, Nicolas; Masoodi, Mojgan; Greenberg, Norman; Gruetter, Rolf; Cuenoud, Bernard (Frontiers in Nutrition, 2018)
Ketones represent an important alternative fuel for the brain under glucose hypo-metabolic conditions induced by neurological diseases or aging, however their metabolic consequences in healthy brains remain unclear. Here we report that ketones can increase the redox NAD+/NADH ratio in the resting brain of healthy young adults. As NAD is an important energetic and signaling metabolic modulator, these results provide mechanistic clues on how nutritional ketosis might contribute to the preservation of brain health.